Hydroelectrostatic hybrid priming stimulates germination performance via ABA and GA regulation: New promising evidence for tomato gene expression - Garcia, Daniel; Zhao, Yinglei; Zhao, Shuo; Ming, Lin Chau [UNESP]; Huang, Danfeng (Elsevier, 2021)
Seed companies and farmers constantly demand seeds with proper agricultural performance. Seed priming technology is a feasible method to efficiently increase the production of agricultural crops by improving the morphophysiological pattern and metabolism of important enzymes, regulating phytohormones and reprogramming gene expression. The present study reports the ability of hydroelectrostatic hybrid priming, an ecofriendly combined method with multiple priming treatments, to enhance the germination indices and vigor of tomato seeds, as well as the effects of priming over a period of time. The dynamic levels of abscisic acid and gibberellins and the transcription levels of eleven genes associated with germination were tracked during the entire priming procedure and seed germination. Hydroelectrostatic hybrid priming enhances the germination index and vigor of tomato seeds, whereas unprimed seeds took longer to complete the germination process. An increase in gibberellin levels and a decrease in abscisic acid levels were detected during the priming procedures, allowing for the weakening of the endosperm cap quickly after sowing. In addition, significant changes in the transcription levels of SlNCED2 and SlDELLA were observed during the priming procedures; both genes play important roles during seed germination. The present investigation also demonstrated a potential synergism associated with the priming procedures, conferring fast germination of tomato seeds via hormone regulation and the reprogramming of gene expression. Regarding the effects of priming over a period of time, the results showed an enhancement of the germination indices and vigor responses of primed seeds compared to primed and unprimed seeds without a storage period. Hence, hydroelectrostatic hybrid priming is a promising and ecofriendly protocol for seed companies and farmers to meet the high demand for tomatoes.
Keywords: Ecofriendly; Longevity; Phytohormone regulation; Solanum lycopersicum; Transcriptional reprogramming